Differential roles of the PKC novel isoforms, PKCdelta and PKCepsilon, in mouse and human platelets. - Pears, C; Thornber, K; Auger, J; Hughes, C; Grygielska, B; Protty, M; Pearce, A; Watson, S (Public Library of Science, 2008)
BACKGROUND: Increasing evidence suggests that individual isoforms of protein kinase C (PKC) play distinct roles in regulating platelet activation. METHODOLOGY/PRINCIPAL FINDINGS: In this study, we focus on the role of two novel PKC isoforms, PKCdelta and PKCepsilon, in both mouse and human platelets. PKCdelta is robustly expressed in human platelets and undergoes transient tyrosine phosphorylation upon stimulation by thrombin or the collagen receptor, GPVI, which becomes sustained in the presence of the pan-PKC inhibitor, Ro 31-8220. In mouse platelets, however, PKCdelta undergoes sustained tyrosine phosphorylation upon activation. In contrast the related isoform, PKCepsilon, is expressed at high levels in mouse but not human platelets. There is a marked inhibition in aggregation and dense granule secretion to low concentrations of GPVI agonists in mouse platelets lacking PKCepsilon in contrast to a minor inhibition in response to G protein-coupled receptor agonists. This reduction is mediated by inhibition of tyrosine phosphorylation of the FcRgamma-chain and downstream proteins, an effect also observed in wild-type mouse platelets in the presence of a PKC inhibitor. CONCLUSIONS: These results demonstrate a reciprocal relationship in levels of the novel PKC isoforms delta and epsilon in human and mouse platelets and a selective role for PKCepsilon in signalling through GPVI.